Застосування активних методів навчання при формуванні професійної компетентності з математичного моделювання інженера-математика - Северина, Наталія Юріївна (НТУ "ХПІ", 2010)
В статье проводится анализ необходимости использования активных методов обучения с целью повышения эффективности формирования профессиональной компетентности по математическому моделированию у будущих инженеров-математиков. Рассмотрены необходимые профессиональные навыки и умения, которые формируются путем применения в учебном процессе деловых игр, тренингов и проблемного обучения.

In the article the analysis in case of active educative methods employment for the purpose of rise in formation profession math-modeling competence performance of future engineermathematicians is conducted. There are racing indispensable professional skills and ability, which are formatting by means of application business games, trainings, problem lectures and practices in the article.
Using active educative methods of formation professional competence of math-modelling for future mathematic engineer
Keywords: формування громадян; підвищення освітнього рівня; кваліфіковані фахівці; інженерна освіта; пізнавальна діяльність; здібності